Optimization of athletes' mental self-regulation under conditions of sports restrictions during the COVID-19 pandemic - Lovyagina, A. E.; Syrykh, I: K.; Tiunova, O. V. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to develop and test a mental self-regulation optimization program for athletes under conditions of restrictions due to the COVID-19 pandemic.